2002
DOI: 10.1002/etc.5620211201
|View full text |Cite
|
Sign up to set email alerts
|

Application of sewage sludge to arable land–soil concentrations of polybrominated diphenyl ethers and polychorinated dibenzo‐p‐dioxins, dibenzofurans, and biphenyls, and their accumulation in earthworms

Abstract: Soils from five agricultural sites, three research sites, and two privately owned farms were analyzed for polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), polychlorinated biphenyls (PCBs), and polybronimated diphenylethers (PBDEs). In soils that had not been treated with sludge (reference soils), the international toxic equivalents (I-TEQs) were 0.6 to 1.5 pg/g dry matter (D.M) for the PCDD/Fs. which are low compared to generally reported background soil levels in Europe. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 34 publications
8
34
2
1
Order By: Relevance
“…Smaller molecular size is considered to be an important factor affecting bioaccumulation. This correlates with other studies where the accumulation of 2,3,7,8-substituted tetra-and penta-chlorinated PCDD/Fs are generally two to three times higher than OCDD/F (Matscheko et al, 2002a(Matscheko et al, , 2002b.…”
Section: Bioaccumulation Of Pcdd/fs By Earthwormssupporting
confidence: 91%
See 2 more Smart Citations
“…Smaller molecular size is considered to be an important factor affecting bioaccumulation. This correlates with other studies where the accumulation of 2,3,7,8-substituted tetra-and penta-chlorinated PCDD/Fs are generally two to three times higher than OCDD/F (Matscheko et al, 2002a(Matscheko et al, , 2002b.…”
Section: Bioaccumulation Of Pcdd/fs By Earthwormssupporting
confidence: 91%
“…Since soils are heterogeneous environmental matrices with varying spatial and temporal distribution of organic carbon, pH, humidity, particle size distribution, the measured PCDD/Fs concentration in the soil is not the same as the environmentally bioavailable concentration, which is also dependent on the duration of contact between compound and soil (aging) and physicochemical properties of the compounds. Therefore knowledge of the site specific uptake and bioaccumulation is necessary for adequate assessment of environmental and human health risks associated with a contaminated site (Belfroid et al, 1995;Matscheko et al, 2002aMatscheko et al, , 2002bLanno et al, 2004). A good supplement to chemical analysis of soil in a site specific risk assessment is investigation of the amount of PCDD/Fs which are bioavailable to earthworms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, few results are available concerning uptake and elimination kinetics of PCDD/Fs in earthworm, while some polycyclic aromatic hydrocarbons (PAHs) with planar structures showed declining uptake rate by worms with increasing contaminant concentration in sediment, and sediment avoidance was observed at high dose of contaminants (Kukkonen and Landrum, 1994;Landrum et al, 2002). Another important consideration is that general lower BSAFs (b1) were obtained for PCDD/Fs in many previous studies (Fagervold et al, 2010;Matscheko et al, 2002;Nakamura et al, 2007), which suggested bioaccumulation of PCDD/Fs may be restricted by some factors such as saturation of the compounds within lipids, bioavailability, as well as the soil characteristics.…”
Section: Bioaccumulation In Earthwormmentioning
confidence: 95%
“…However, grazing also enhances soil intake by herbivores (soil particles on vegetation, root intake, Abrahams and Steigmajer, 2003) resulting in an increased exposure to gastrointestinal parasites (Stromberg, 1997) and environmental contaminants (Laurent et al, 2005). Although ingested soil may be a source of mineral nutrients for animals (Thornton and Abrahams, 1983), several studies pointed out soil as being one of the main matrices for pollutants transfer to outside-reared animals (Beresford and Howard, 1991;Fries, 1995;Matscheko et al, 2002). Lipophilic properties of the persistent organic pollutants are responsible for their adsorption on soil components, which enables soil to retain and accumulate pollutants in the horizon surface longer than the other matrices (also called memory effect) (Jones et al, 1989;Duarte-Davidson and Jones, 1996).…”
Section: Introductionmentioning
confidence: 99%